(untitled) (Asian Education Studies, 2018)
The study examined the challenges of the realisation of a world-class university at Kwara State University, Malete, Nigeria. Two research questions and two null hypotheses were formulated for the study. Descriptive survey research design was adopted for the study. The population of the study was 1,078 lecturers out of which 245 lecturers were sampled. Challenges of the Realization of World-class University Questionnaire (CRSWUQ) constructed by the researchers were used for data collection for the study. Percentage was used to answer the research questions while Mann Whitney U-test was used to test the hypotheses at 0.05 level of significance. The findings revealed among others that: world class status of a university is simply about the international recognition of the university. A world class university has world class departments, diversified sources of income, sound financial base and always benchmarked with top universities world-wide. Lack of physical infrastructure which is obviously the most visible part of the university, the pressure of publish or perish culture which undermines the quality of research and absence of public financial support are some of the challenges that could hinder the world-class status of Kwara State University. Based on the findings, it was recommended that the state government, KWASU management, academic staff and the entire university community should work together to overcome the identified challenges that could hinder the realization of a world class status of KWASU.